KOMUNIKASI RITUAL DALAM PUJAWALI NUWUR TIRTA DI PURA LINGKUK BUNI KOTA MATARAM - Putri, Gusti Ayu Dheananda Sagitha; Wirawan, I Wayan Ardhi (IAHN Gde Pudja Mataram, 2025)
This article focuses on ritual communication in the nuur tirta tradition of a series of pujawali at Pura Lingkuk Buni in Mataram City. This article was written based on research conducted using qualitative descriptive methods to explain aspects related to ritual communication in the nuur tirta tradition. Based on the results of the study, it was found that the existence of Pura Lingkuk Buni is related to the initiative to purify a spring called engeran. The nuur tirta process is carried out during the pujawali on purnama sasi kasa which comes from temples with the same name as the pelinggih in the temple. The nuur tirta process of several temples to be placed in each pelinggih at Pura Lingkuk Buni is a symbolic communication process that involves aspects of upakara, sacred utterances, and religious behavior. The upakara aspect is indicated by the use of ceremonial facilities that are full of symbols. Ritual communication in sacred utterances through mantras, puja, prayers, and the like in the implementation of pujawali. Ritual communication in the aspect of religious behavior is implemented through the act of dancing, ngayah nuur tirta, and organizing ceremonies